High-flame-retardant epoxy adhesive as well as preparation method and application thereof

By adding MXene nanosheets and phosphorus-based flame retardant to the epoxy resin-based adhesive, a high flame retardant epoxy adhesive is formed, which solves the problem of unsatisfactory flame retardant performance of existing adhesives and achieves a comprehensive optimization effect of high flame retardancy, bonding strength and impact strength.

CN119875561APending Publication Date: 2025-04-25JINAN NORTH TAIHE NEW MATERIAL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411796308.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The bonding strength, thermal stability and flame retardant properties of existing epoxy resin-based adhesives are not ideal, especially in cases where fire resistance is required.

Method used

MXene nanosheets and phosphorus-based flame retardant are used as synergistic flame retardant and added to the epoxy resin-based adhesive to form a high flame retardant epoxy adhesive. The adhesive is prepared by mechanical stirring and blending method, and has good flame retardancy, bonding strength and impact strength.

Benefits of technology

Adhesives that achieve high flame retardant performance can stably reach B1 (C) flame retardant grade, and have excellent adhesive strength and impact strength. They are suitable for furniture, wood, aerospace, military and electronic products and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875561A_ABST
    Figure CN119875561A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flame-retardant materials, in particular to a high-flame-retardant epoxy adhesive as well as a preparation method and application thereof, and the adhesive is prepared from the following raw materials: MXene nanosheets, a phosphorus flame retardant and an epoxy resin-based adhesive; the MXene nanosheet and the organic phosphorus flame retardant are used as synergistic flame retardants to be added into the epoxy resin-based adhesive; the modified epoxy flame-retardant adhesive prepared from the components is good in flame retardance, excellent in bonding strength and impact strength and high in practical application value in the fields of furniture wood, aerospace, military industry and electronic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new flame retardant materials, and in particular to a highly flame retardant epoxy adhesive and a preparation method and application thereof. Background Art

[0002] Epoxy resin has been widely used in the adhesive field due to its excellent mechanical properties, electrical insulation and chemical stability. However, epoxy resin itself is flammable, which limits its application in some occasions that require fire resistance. Therefore, epoxy resin flame retardant adhesive came into being.

[0003] In order to improve the flame retardant properties of epoxy resin, the existing technology usually adopts the method of adding halogen-containing flame retardants, which can release gases such as hydrogen halide during combustion to play a flame retardant role. However, halogen-containing flame retardants will produce toxic and corrosive gases during combustion, which are harmful to the environment and human health, and their flame retardant efficiency is limited.

[0004] With the improvement of environmental protection and safety requirements, halogen-free flame retardants have gradually become a research hotspot. Common halogen-free flame retardants include phosphorus flame retardants, nitrogen flame retardants, silicon flame retardants and inorganic flame retardants (such as aluminum hydroxide, magnesium hydroxide, etc.). These flame retardants play a flame retardant role through different mechanisms, such as phosphorus flame retardants forming a carbon layer when burning to block heat and oxygen; nitrogen flame retardants release non-flammable gases to dilute the concentration of combustible gases. At the same time, the research on epoxy flame retardant adhesives also involves the compatibility of flame retardants with epoxy resins, the impact on other properties of adhesives (such as bonding strength, corrosion resistance, heat resistance, etc.), and how to achieve high-efficiency, environmentally friendly, and comprehensive flame retardant adhesives by optimizing the formula and preparation process. In recent years, the development of nanotechnology has also brought new ideas for epoxy flame retardant adhesives. Nanomaterials (such as nanoclays, carbon nanotubes, etc.) have unique physical and chemical properties and can improve the flame retardant properties and comprehensive properties of epoxy resins.

[0005] Therefore, combining the existing new technologies to provide a highly flame retardant epoxy adhesive has become the focus of the inventor's research. Summary of the invention

[0006] In order to overcome the problems of unsatisfactory bonding strength, thermal stability and flame retardant properties of epoxy resin-based adhesives in the prior art, the purpose of the present invention is to provide a highly flame-retardant epoxy adhesive and a preparation method and application thereof. The adhesive raw materials include MXene nanosheets, a phosphorus-based flame retardant and an epoxy resin-based adhesive; the MXene nanosheets and the organic phosphorus-based flame retardant are added to the epoxy resin-based adhesive as synergistic flame retardants respectively; the modified epoxy flame retardant adhesive using the above composition not only has good flame retardancy, but also has excellent bonding strength and impact strength, and has high practical application value in the fields of furniture wood, aerospace, military industry and electronic products.

[0007] The modified epoxy flame retardant adhesive provided by the present invention has good flame retardant performance, and can stably reach the B1 (C) flame retardant grade by adding a small amount of flame retardant. The high flame retardant epoxy adhesive provided by the present invention has good fluidity, simple mixing, simple preparation, and strong process adaptability. After heating, a curing effect can be formed between the flame retardant and the epoxy component to enhance the adhesion. The bonding strength of the flame retardant plywood prepared with the flame retardant as the raw material can reach the Class III bonding strength requirement.

[0008] The purpose of the present invention is achieved through the following technical solutions: A highly flame-retardant epoxy adhesive, comprising, by weight, 2-5 parts of MXene nanosheets, 5-10 parts of a phosphorus-based flame retardant, and 180-200 parts of an epoxy resin-based adhesive; the MXene nanosheets and the organic phosphorus-based flame retardant are synergistic flame retardants, which are added to the epoxy resin-based adhesive respectively; the viscosity of the highly flame-retardant epoxy adhesive is 4000-5000 mPa·s.

[0009] The preparation method of the MXene nanosheets is as follows: dissolving fluoride in hydrochloric acid, adding MAX, stirring, centrifuging, washing the precipitate until the pH of the supernatant is ≥ 6; taking the precipitate, adding deionized water, ultrasonic treatment, centrifuging and collecting the upper suspension to obtain a MXene dispersion, and the MXene dispersion is then used to obtain MXene nanosheets. There is no special requirement for the amount of deionized water, as long as the dispersion is prepared by ultrasonic dispersion.

[0010] Preferably, the MAX is Ti3AlC2, the ratio of hydrochloric acid, fluoride, and MAX is (10-150) mL: (1-5) g: (1-6) g; the concentration of the hydrochloric acid is 4-12 mol / L; More preferably, the ratio of hydrochloric acid, fluoride and MAX is (20-100) mL: (1.5-3) g: (2-4) g, and the concentration of hydrochloric acid is 8-12 mol / L.

[0011] The fluoride is selected from lithium fluoride.

[0012] Preferably, the stirring conditions after adding MAX are 30-48°C and 12-72 h; more preferably, 40°C and 24 h; the centrifugal conditions after stirring are 3000-4000 r / min and 3-8 min; more preferably, 3500 r / min and 5 min.

[0013] Preferably, the ultrasonic treatment time is 20 to 60 min, and the ultrasonic power can be set at a conventional setting. In the embodiment of the present invention, it is set to 240W.

[0014] Preferably, the centrifugation conditions after ultrasonic treatment are a rotation speed of 3000-4000 r / min and a time of 20-60 min; more preferably, a rotation speed of 3500 r / min and a time of 20-30 min.

[0015] Preferably, the freeze-drying temperature is -50°C. There is no special requirement for the freeze-drying time, and the freeze-drying can be carried out until the volatilization is complete and a dry product is obtained.

[0016] The phosphorus-based flame retardant is an organic phosphorus-based flame retardant; further, the organic phosphorus-based flame retardant is a phosphonate flame retardant.

[0017] MXene nanosheets have catalytic properties and physical barrier properties, and bisphenol A bis(diphenyl phosphate) has the functions of catalyzing carbon formation, terminating free radical reactions and releasing flame-retardant gases. The combination of the two can effectively improve the flame retardant properties of epoxy resin adhesives and increase the limiting oxygen index of epoxy resin adhesives.

[0018] The epoxy resin-based adhesive is a mixture of component A and component B, wherein component A is an epoxy composite monomer, component B is an amine curing agent, and the mass ratio of component A to component B is (0.8-1.2):1, more preferably 1:1.

[0019] Preferably, the phosphonate flame retardant is bisphenol A bis(diphenyl phosphate), component A is a mixture of phenolic epoxy resin and epoxy silane coupling agent KH560; and component B is polyether amine.

[0020] Furthermore, component A includes 90-100 parts of phenolic resin and 5-10 parts of epoxy silane coupling agent KH560 by weight.

[0021] The above-mentioned epoxy composite monomer can form a cross-linking effect with MXene nanosheets and BDP, which has a positive effect on thermal stability and bonding strength.

[0022] More preferably, component A includes 90 parts of novolac epoxy resin and 10 parts of epoxy silane coupling agent KH560 by weight.

[0023] In addition, the inventors also provided a method for preparing the above-mentioned highly flame-retardant epoxy adhesive, which is specifically obtained by mechanically stirring and blending the epoxy resin-based adhesive, phosphorus-based flame retardant and MXene nanosheets for 2 hours. The viscosity of the obtained adhesive is 4000-5000 mPa·s.

[0024] The highly flame-retardant epoxy adhesive provided by the present invention can be applied to the furniture wood field, such as the pressing of plywood, and the veneer is coated using conventional processes with an application amount of 120g / m 2The mixture is paved, pre-pressed, pre-heated and pressed by penetrating steam spraying, and hot-pressed to prepare flame-retardant plywood; the hot-pressing temperature is 110°C, the time is 180s, and the pressure is 2.5MPa.

[0025] In addition, the highly flame-retardant epoxy adhesive can also be used in the fields of aerospace, military industry and electronic products. For example, it can be used to bond honeycomb structures in aircraft to replace rivet connections in aircraft, so that the fuselage has better quality and strength; it can be used for bonding structures such as car bodies, interiors, windshields, clutches, brake pads, chassis, etc.; it can be used as a packaging adhesive for electronic products, etc.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The highly flame-retardant epoxy adhesive provided by the present invention innovatively introduces MXene nanosheets and bisphenol A bis(diphenyl phosphate) (BDP) composite flame retardant. The MXene nanosheets have catalytic properties and physical barrier properties, and bisphenol A bis(diphenyl phosphate) (BDP) has the functions of catalyzing carbonization, terminating free radical reactions and releasing flame-retardant gases. The two can synergistically effectively improve the flame retardant properties of epoxy resin adhesives and increase the limiting oxygen index of epoxy resin adhesives.

[0027] (2) In the highly flame-retardant epoxy adhesive component provided by the present invention, the epoxy composite monomer can form a cross-linking effect with the MXene nanosheets and BDP, which has a positive effect on thermal stability and bonding strength. The prepared flame-retardant plywood has a bonding strength of >50MPa, which can meet the Class III bonding strength requirements.

[0028] (3) The preparation method of the highly flame-retardant epoxy adhesive provided by the present invention can be completed by a simple stirring and blending method, and the process is simple.

[0029] (4) The flame retardant used in the present invention does not contain halogen, the process is environmentally friendly and safe, it is conducive to industrial promotion and application, and the product quality is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 X-ray diffraction patterns of MXene and raw material Ti3AlC2 prepared in Example 1 of the present invention; Figure 2 The cross-sectional SEM image and the corresponding EDS scanning image of the adhesive coating film after curing in Example 1 of the present invention, wherein a is the SEM image, b is the C element distribution map, c is the O element distribution map, d is the Si element distribution map, e is the P element distribution map, and f is the Ti element distribution map; Figure 3The cross-sectional SEM image and the corresponding EDS scanning image of the adhesive coating after curing in Comparative Example 2 of the present invention, wherein a is the SEM image, b is the O element distribution image, c is the Si element distribution image, d is the C element distribution image, and e is the P element distribution image; Figure 4 These are the cross-sectional SEM images and corresponding EDS scan images of the adhesive coating after curing in Comparative Example 3 of the present invention, wherein a is the SEM image, b is the C element distribution map, c is the F element distribution map, d is the O element distribution map, e is the Si element distribution map, and f is the Ti element distribution map. DETAILED DESCRIPTION

[0031] Now, various exemplary embodiments of the present invention are described in detail in conjunction with the accompanying drawings. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0032] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0033] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0034] Unless otherwise specified, the materials and reagents used in the embodiments are generally commercially available products.

[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0036] Example 1 A highly flame-retardant epoxy adhesive and its preparation method and application (1) Preparation of MXene flame retardant filler Measure 60mL of 9 mol / L hydrochloric acid into a polytetrafluoroethylene beaker, then weigh 2g of LiF and pour it into the hydrochloric acid, stirring until completely dissolved; weigh 2g of Ti3AlC2 and add it to the above mixed solution, stirring at 40°C for 24h; then centrifuge (3500r, 5min), wash the precipitate with deionized water for several times until the pH of the supernatant is ≥ 6. Keep the precipitate, add 500mL of deionized water to the precipitate, ultrasonicate at 240w for 60min, centrifuge at 3500r / min for 30min, collect the upper suspension, that is, the desired MXene dispersion, and then freeze-dry at -50°C until it is completely volatilized to obtain the MXene flame retardant filler.

[0037] X-ray diffraction (XRD) was used to identify the structure of the above-mentioned MXene flame retardant filler: a D / MAX2200 / PC X-ray diffractometer (Rigaku, Japan) was used to analyze the crystal forms of MAX and MXene; the diffraction target was CuKα (k = 1.5406Å), the test angle scanning range was 5 ~ 80°, and the scanning speed was 5° / min.

[0038] The X-ray diffraction patterns of MXene and raw material Ti3AlC2 in this example are shown in Figure 1 .like Figure 1 As shown, the (002) diffraction peak in MAX moved significantly from 9.60° to 6.76°, which means that the interplanar spacing increased from 9.20 Å to 13.06 Å, indicating that the Al layer in the MAX phase was successfully etched away, MXene nanosheets were successfully prepared, and MXene was successfully etched into a single-layer or few-layer structure.

[0039] (2) Preparation of MXene-modified flame-retardant adhesives Phenolic epoxy resin (90 g) and epoxy silane coupling agent KH560 (10 g) were used as component A (main agent), polyetheramine (100 g) was used as component B (curing agent), 5 g of the MXene flame retardant prepared in step (1) was used as filler, and 9 g of bisphenol A bis(diphenyl phosphate) was used. The above components were mechanically stirred and blended for 2 h to prepare a flame retardant adhesive with a viscosity of 4605 mPa·s.

[0040] (3) Pressing of flame retardant plywood The size is 50mm×500mm×2m, and the density is 0.85g / cm 3 The poplar wood is used as a single board, and the flame retardant adhesive prepared above is coated according to the conventional process, and the amount of adhesive applied is 120g / m 2 The mixture is paved, pre-pressed, pre-heated and pressed by penetrating steam spraying, and hot-pressed to prepare flame-retardant plywood; the hot-pressing temperature is 110°C, the time is 180s, and the pressure is 2.5MPa.

[0041] Figure 2 Shown are the cross-sectional SEM images and EDS scans of the film (thickness 1 um, curing conditions 100°C, 5 h) prepared by the adhesive formulation used in Example 1 by the blade coating method. The SEM image shows that the MXene nanosheets are successfully and evenly introduced into the epoxy resin adhesive. From the EDS scan, it can be observed that the phosphate ester is evenly distributed in the adhesive.

[0042] Example 2 A highly flame-retardant epoxy adhesive and its preparation method and application (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0043] (2) Phenolic epoxy resin (90 g) and epoxy silane coupling agent KH560 (10 g) were used as component A (main agent), polyetheramine (100 g) was used as component B (curing agent), 5 g of the MXene flame retardant prepared in step (1), and 8 g of bisphenol A bis(diphenyl phosphate) were mechanically stirred and blended for 2 h to prepare a flame retardant adhesive with a viscosity of 4588 mPa·s.

[0044] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0045] Example 3 A highly flame-retardant epoxy adhesive and its preparation method and application (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0046] (2) Phenolic epoxy resin (90 g) and epoxy silane coupling agent KH560 (10 g) were used as component A (main agent), polyetheramine (100 g) was used as component B (curing agent), 4 g of the MXene flame retardant prepared in step (1), and 7 g of bisphenol A bis(diphenyl phosphate). The above components were mechanically stirred and blended for 2 h to prepare a flame retardant adhesive with a viscosity of 4507 mPa·s.

[0047] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0048] Example 4 A highly flame-retardant epoxy adhesive and its preparation method and application (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0049] (2) Phenolic epoxy resin (95 g) and epoxy silane coupling agent KH560 (5 g) were used as component A (main agent), polyetheramine (100 g) was used as component B (curing agent), 3 g of the MXene flame retardant prepared in step (1), and 6 g of bisphenol A bis(diphenyl phosphate). The above components were mechanically stirred and blended for 2 h to prepare a flame retardant adhesive with a viscosity of 4448 mPa·s.

[0050] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0051] Example 5 A highly flame-retardant epoxy adhesive and its preparation method and application (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0052] (2) Use phenolic epoxy resin (90 g) and epoxy silane coupling agent KH560 (10 g) as component A (main agent), polyetheramine (100 g) as component B (curing agent), 2 g of the MXene flame retardant prepared in step (1), and 6 g of bisphenol A bis(diphenyl phosphate). Mechanically stir and blend the above components for 2 h to prepare a flame retardant adhesive with a viscosity of 4335 mPa·s.

[0053] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0054] Comparative Example 1 (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0055] (2) Use phenolic epoxy resin (90 g) as component A (main agent), polyetheramine (100 g) as component B (curing agent), add 5 g MXene flame retardant filler and 9 g bisphenol A bis(diphenyl phosphate), blend the above components to prepare a flame retardant adhesive with a viscosity of 4518 mPa·s.

[0056] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0057] Comparative Example 2 (1) Phenolic epoxy resin (90 g) and epoxy silane coupling agent KH560 (10 g) were used as component A (main agent), polyetheramine (100 g) was used as component B (curing agent), no MXene flame retardant was added, and bisphenol A bis(diphenyl phosphate) 28 g was added. The above components were mechanically stirred and blended for 2 h to prepare a flame retardant adhesive with a viscosity of 4368 mPa·s.

[0058] (2) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0059] Figure 3 Shown are the cross-sectional SEM image and EDS scan image of the adhesive coating of Comparative Example 2 after curing. Since no MXene nanosheets were added in Comparative Example 2, it can be observed from the SEM image that the typical resin surface is a smooth plane, and from the EDS scan image it can be observed that the phosphate ester is evenly distributed in the adhesive. Since no MXene was added in Comparative Example 2, the EDS cannot scan the distribution of the Ti element.

[0060] Comparative Example 3 (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0061] (2) Phenolic epoxy resin (90 g) and epoxy silane coupling agent KH560 (10 g) were used as component A (main agent), polyetheramine (100 g) was used as component B (curing agent), 6 g of MXene flame retardant was added, and bisphenol A bis(diphenyl phosphate) was not added. The above components were mechanically stirred and blended for 2 h to prepare a flame retardant adhesive with a viscosity of 4571 mPa·s.

[0062] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0063] Figure 4 Shown are the cross-sectional SEM image and EDS scan image of the adhesive coating of Comparative Example 3 after curing. The SEM image shows that the MXene nanosheets are successfully introduced into the epoxy resin adhesive. From the EDS scan image, it can be observed that the MXene is evenly distributed in the adhesive. Since no phosphorus-based flame retardant is added in Comparative Example 3, the P distribution cannot be scanned by EDS.

[0064] Comparative Example 4 (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0065] (2) 90 g of phenolic epoxy resin and 10 g of epoxy silane coupling agent KH560 were used as component A (main agent), 100 g of polyetheramine was used as component B (curing agent), 0.5 g of the MXene flame retardant prepared in step (1), and 25 g of bisphenol A bis(diphenyl phosphate) were added. The above components were mechanically stirred and blended for 2 h to prepare a flame retardant adhesive with a viscosity of 4398 mPa·s.

[0066] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0067] Comparative Example 5 (1) Preparation of MXene flame retardant filler The method for preparing MXene flame retardant filler is the same as that in Example 1.

[0068] (2) Use phenolic epoxy resin (90 g) and epoxy silane coupling agent KH560 (10 g) as component A (main agent), polyetheramine (100 g) as component B (curing agent), 1 g of the MXene flame retardant prepared in step (1), and 25 g of bisphenol A bis(diphenyl phosphate). Mechanically stir and blend the above components for 2 h to prepare a flame retardant adhesive with a viscosity of 4425 mPa·s.

[0069] (3) Pressing of flame retardant plywood The method is the same as that of pressing the flame retardant plywood in Example 1.

[0070] Experimental example The bonding strength of the flame retardant plywood prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels"; the impact strength of the flame retardant plywood prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T 9846-2015 "Ordinary plywood"; the oxygen index of the flame retardant plywood prepared in Examples 1-5 and Comparative Examples 1-5 was tested according to GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test", and the test results are shown in Table 1.

[0071] Table 1 Test results of epoxy adhesives and flame retardant plywood prepared in Examples 1-5 and Comparative Examples 1-5 Epoxy resin based adhesive (parts) MXene (parts) Bisphenol A bis(diphenyl phosphate) (parts) Viscosity (mPa·s) Bonding strength (MPa) Impact strength (MPa) Oxygen Index (LOI%) Example 1 200 5 9 4605 35.8 36.8 35.5 Example 2 200 5 8 4588 35.1 35.8 34.2 Example 3 200 4 7 4507 34.9 34.6 33.6 Example 4 200 3 6 4448 33.7 33.5 32.8 Example 5 200 2 6 4335 32.3 33.8 33.8 Comparative Example 1 190 (excluding KH560) 5 9 4518 30.3 33.1 30.2 Comparative Example 2 200 0 28 4368 31,1 32.2 29.6 Comparative Example 3 200 6 0 4571 26.9 27.9 26.8 Comparative Example 4 200 0.5 25 4398 27.2 28.9 27.8 Comparative Example 5 200 1 25 4425 28.5 30.1 29.8 It can be seen from the above table that compared with the comparative example, the embodiment has better oxygen index and impact strength, and has higher bonding strength, and its flame retardant and bonding properties have obvious advantages. However, since the comparative example does not add BDP or MXene, or the ratio of the two is not within the scope of the present invention, its bonding strength, impact strength and flame retardant properties are relatively poor. In addition, when KH560 is not present in the component, the bonding strength, impact strength and oxygen index of the adhesive all show a certain degree of decrease, which indicates that KH560 can effectively enhance the interface between MXene and epoxy resin matrix, thereby affecting the overall performance.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly flame retardant epoxy adhesive, characterized in that: The components include 2-5 parts of MXene nanosheets, 5-10 parts of phosphorus flame retardants, and 180-200 parts of epoxy resin-based adhesives by weight; the viscosity of the highly flame-retardant epoxy adhesive is 4000-5000 mPa·s.

2. The highly flame-retardant epoxy adhesive according to claim 1, characterized in that: The preparation method of the MXene nanosheet is as follows: dissolving fluoride in hydrochloric acid, adding MAX, stirring, centrifuging, washing the precipitate until the pH value of the supernatant is ≥6; taking the precipitate, adding deionized water, ultrasonically treating, centrifuging and collecting the upper suspension to obtain a MXene dispersion, and freeze-drying the MXene dispersion to obtain the MXene nanosheet.

3. The highly flame-retardant epoxy adhesive according to claim 2, characterized in that: The MAX is Ti3AlC2, the ratio of hydrochloric acid, fluoride and MAX is (10-150) mL: (1-5) g: (1-6) g, and the concentration of hydrochloric acid is 4-12 mol / L.

4. The highly flame-retardant epoxy adhesive according to claim 3, characterized in that: The stirring conditions after adding MAX are as follows: temperature 30-48°C, time 12-72 h; the centrifugal conditions after stirring are as follows: speed 3000-4000 r / min, time 3-8 min; the ultrasonic treatment time is 20-60 min; the centrifugal conditions after ultrasonic treatment are as follows: speed 3000-4000 r / min, time 20-60 min.

5. The highly flame retardant epoxy adhesive according to any one of claims 1 to 4, characterized in that: The phosphorus-based flame retardant is a phosphonate flame retardant; the epoxy resin-based adhesive is a mixture of component A and component B, component A is an epoxy composite monomer, component B is an amine curing agent, and the mass ratio of component A to component B is (0.8-1.2):

1.

6. The highly flame-retardant epoxy adhesive according to claim 5, characterized in that: The phosphonate flame retardant is bisphenol A bis(diphenyl phosphate); component A is a mixture of phenolic epoxy resin and epoxy silane coupling agent KH560; and component B is polyether amine.

7. The highly flame-retardant epoxy adhesive according to claim 6, characterized in that: Component A includes 90-100 parts of phenolic resin and 5-10 parts of epoxy silane coupling agent KH560 by weight.

8. The highly flame-retardant epoxy adhesive according to claim 7, characterized in that: Component A includes 90 parts of phenolic epoxy resin and 10 parts of epoxy silane coupling agent KH560 by weight; the mass ratio of component A to component B is 1:

1.

9. A method for preparing the highly flame-retardant epoxy adhesive according to any one of claims 1 to 4, characterized in that: The epoxy resin-based adhesive, the phosphorus-based flame retardant and the MXene nanosheets are mixed to obtain the adhesive.

10. Use of the highly flame retardant epoxy adhesive according to any one of claims 1 to 4 in plywood pressing.

Citation Information

Patent Citations

  • Nano-modified flame-retardant epoxy electronic pouring sealant and preparation method thereof

    CN104789177A

  • Halogen-free flame retardation electronic pouring sealant

    CN106010399A

  • Ternary nano-composite flame retardant, flame-retardant epoxy resin and preparation method of flame-retardant epoxy resin

    CN113845695A

  • MXene nanosheet modified phosphorus-nitrogen single-component intumescent flame retardant as well as preparation method and application thereof

    CN114507380A

  • MXene-based unsaturated resin flame-retardant material coated with sulfur-containing hydrogel and preparation method of MXene-based unsaturated resin flame-retardant material

    CN117264395A